2011
DOI: 10.1038/mt.2010.248
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde Axonal Transport of AAV2-GDNF in Rat Basal Ganglia

Abstract: We elucidated the effects of parkinsonian degeneration on trafficking of AAV2-GDNF in the nigro-striatum (nigro-ST) of unilaterally 6-hydroxydopamine (6-OHDA)-lesioned rats. Vector infused into striatum (ST) was transported to substantia nigra (SN), both pars compacta (SNc), and pars reticulata (SNr). In the lesioned hemisphere, glial cell line-derived neurotrophic factor (GDNF) immunoreactivity was only found in SNr consistent with elimination of SNc dopaminergic (DA) neurons by 6-OHDA. Further analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 38 publications
4
71
0
Order By: Relevance
“…We have previously reported that the AAV2-hAADC distribution appears to broaden slowly over time in NHP, resulting in a larger coverage of target regions (Daadi et al, 2006). In addition, because AAV2 vector is transported anterogradely through the axons (Ciesielska et al, 2011), we also found AADC expression in structures outside the striatum such as the globus pallidus, subthalamic nucleus, substantia nigra pars reticulata, and thalamus.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We have previously reported that the AAV2-hAADC distribution appears to broaden slowly over time in NHP, resulting in a larger coverage of target regions (Daadi et al, 2006). In addition, because AAV2 vector is transported anterogradely through the axons (Ciesielska et al, 2011), we also found AADC expression in structures outside the striatum such as the globus pallidus, subthalamic nucleus, substantia nigra pars reticulata, and thalamus.…”
Section: Discussionmentioning
confidence: 53%
“…2b). We noted some AADC expression in neuronal cell bodies and fibers in structures within the infused hemisphere, such as in the internal and external globus pallidus, subthalamic nucleus, and substantia nigra pars reticulata (data not shown), indicating anterograde transport of the vector (Ciesielska et al, 2011).…”
Section: Image-guided Aav2 Delivery 213mentioning
confidence: 99%
“…Earlier a dissociative expression of Ad lacZ gene transfection was found in ischemic rat brain [17]. It has been reported by others, too, that the transfection efficiency and transgene expression can be dependent on the lesion and tissue [19,20]. Therefore, it is likely that the transfection efficiency of gene vectors in the target cells and tissues would be affected by methodological parameters and physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies ( Jakobsson et al, 2003;Ciesielska et al, 2011;Richardson et al, 2011;Drinkut et al, 2012) have previously reported that striatal transgene expression targeted to neurons resulted in transgene products in the SNpc/pr, the globus pallidus, and the subthalamic nucleus, in both lesioned and unlesioned hemispheres. This was possibly because of retrograde delivery from striatal dopaminergic nerve terminals to the cell bodies in the SNpc (Tomac et al, 1995) and anterograde axonal transport from striatal neurons to the afferent regions via the indirect pathway, plus axonal sprouting between the two striatal hemispheres (Ciesielska et al, 2011;Richardson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This was possibly because of retrograde delivery from striatal dopaminergic nerve terminals to the cell bodies in the SNpc (Tomac et al, 1995) and anterograde axonal transport from striatal neurons to the afferent regions via the indirect pathway, plus axonal sprouting between the two striatal hemispheres (Ciesielska et al, 2011;Richardson et al, 2011). These off-target effects may provide some advantages in GDNF application for PD treatment, but levels of GDNF transported indirectly to these afferent regions are unpredictable, particularly when higher vector doses or longer expression times are required (Bartus et al, 2011;Drinkut et al, 2012).…”
Section: Discussionmentioning
confidence: 99%